Evaluation of Air-Gap Stacked Capacitive Antennas for Lightning Remote Sensing - Seah B.Y.; Ahmad M.R.; Ong Y.J.; Shairi N.A.; Periannan D.; Sabri M.H.M.; Esa M.R.M.; Abdul-Malek Z.; Mohammad S.A.; Aziz M.Z.A.A.; Yusop N.; Ismail M.M.; et al. (Institute of Physics Publishing, 2023)
Capacitive sensors; Climate change; Electric fields; Lightning; Plates (structural components); Remote sensing; Antenna design; Antenna performance; Antenna structures; Comparison result; Different structure; Frequency-shifting; Pulse amplitude; Stacked antennas; Slot antennas